Existence and uniqueness of classical solution to Darboux problem together with nonlocal conditions - Byszewski, Ludwik (Annales Mathematicae Silesianae, 2013)
The existence and uniqueness of a classical solution to a semilinear hyperbolic differential Darboux problem together with semilinear nonlocal conditions in a bounded domain are studied. The Banach fixed point theorem is applied.